Does presence of common bile duct stones in patients with acute biliary pancreatitis affect the severity of illness or laboratory findings? - Emrah Alper; Behlül BAYDAR; Sezgin VATANSEVER; Zafer BUYRAÇ; Fatih Aslan; Zehra Akpınar; M.Kadir AKSÖZ; Serdar AKÇA; Belkıs Ünsal (Turkish Journal of Gastroenterology, 2019)
-